The Need Analysis for E-Learning Based on Massive Open Online Course (MOOC) for High School Students - Andika Febrian; Y Yennita; Zuhdi Ma’ruf (Jurnal Penelitian Pendidikan IPA, 2021)
The rapid development of the era demands that the world of education also be involved. Because along with the development of the times, education must experience innovation and adapt to advances in technology and information to exist and maintain its quality. MOOC is a system that integrates education and technology. Through this system, learning is presented that is interesting, effective, and easily accessible to anyone. This survey research was conducted as a first step in developing MOOC-based e-learning for high school students. The benefit of this research is that we will get what students currently need in learning physics online based on MOOC. This requirement analysis is seen based on two indicators: analysis of learning problems and analysis of students. Based on the results of this study, it was found that there is a need for MOOC-based e-learning for high school students with a high category level. Thus, the steps that will be made after this are developing learning tools to meet these needs